Taxonomic, Functional, and Phylogenetic Diversity of Bats in Urban and Suburban Environments in Southern México - Miguel Briones-Salas; Gabriela E. Medina-Cruz; Cintia Natalia Martin-Regalado (Diversity)
Urbanization is one of the leading causes of habitat loss, which has increased significantly in tropical regions in recent years, leading to the loss of species, their ecological functions, and evolutionary history. To determine the effect of urbanization on the diversity of bat communities in urban and suburban environments, we analyzed the α and β taxonomic, functional, and phylogenetic diversities at four sites along urbanization gradients surrounding a rapidly expanding city (Oaxaca City) in southern Mexico. We recorded bats using conventional techniques such as mist nets and acoustic monitoring. We calculated the diversity of bats in four sites with different urbanization conditions: urban (1), suburban (1), and rural (2). To assess the degree of total differentiation and components of bat turnover and nestedness between sites, we calculated the β taxonomic, functional, and phylogenetic diversities. A total of 33 bat species were recorded. The highest taxonomic and functional diversity was observed in the Center of Oaxaca (the site with the highest level of urbanization). In contrast, the highest phylogenetic diversity was found in the West (the site with the lowest level of urbanization). The total β taxonomic diversity was higher than the functional and phylogenetic diversity. Regarding the contributions of turnover and nestedness, turnover made a more significant contribution than nestedness to the taxonomic and phylogenetic β diversity. In contrast, functional nestedness contributed more to the functional β diversity than turnover. Tadarida brasiliensis, Desmodus rotundus, Sturnira hondurensis, and S. parvidens were recorded in all three urbanization conditions. In the most urbanized site, four Myotis species were recorded: M. fortidens, M. keaysi, M. thysanodes, and M. velifer. We suggest that the analysis of different dimensions of diversity is essential and should be considered to strengthen conservation strategies; moreover, we suggest the preservation of native vegetation mosaics and water bodies within the city to maintain bat diversity.